Le Dernier Duel de Ridley Scott : corps médiévaux à l’épreuve du genre - Caroline Masoch (Mise au Point)
This article analyses Ridley Scott’s film The Last Duel, released in 2021, from the perspective of the gendered body. The latest opus by the English film-maker depicts the actors of medieval society in a way that takes account of the most recent studies on gender as applied to the Middle Ages. The Last Duel is a successful popularisation of these studies, respecting their nuances and complexities. The film also bears witness to the female gaze on the screen and is part of the renewed vision of the female body on the screen.